A method for preparing ultrapure high-purity citric acid
By combining nanofiltration with ion exchange resin, the problem of removing metal ions from citric acid was solved, enabling the preparation of ultra-clean, high-purity citric acid, reducing costs and extending resin life.
Patent Information
- Application Number
- CN202211565317.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-07
AI Technical Summary
Existing citric acid purification processes are insufficient to effectively remove metal ions, making it impossible to produce ultra-clean, high-purity citric acid. Domestically produced citric acid is unlikely to meet the standard of metal ion content <1 ppb.
By organically coupling nanofiltration technology with ion exchange resin method, monovalent light metal ions in citric acid solution are removed by nanofiltration, and impurities in citric acid are deeply removed by combining anion and cation exchange resins and mixed bed polishing resin, so as to prepare ultra-clean high-purity citric acid.
This method achieves a metal ion content of <1 ppb in citric acid, extends the service life of ion exchange resins, reduces process costs, and provides an economical and feasible method for producing ultra-clean, high-purity citric acid.
Abstract
Description
Technical Field
[0001] The invention relates to the field of deep processing of citric acid, and in particular to a method for preparing ultra-clean high-purity citric acid. Background Art
[0002] Citric acid is a common tricarboxylic acid organic acid, which is widely used in food industry, fine chemicals, medicine, environmental protection and other fields.
[0003] Ultra-clean high-purity citric acid refers to high-purity citric acid with extremely low content of metal ions and other anions (metal ion content <1ppb), which is mainly used in the field of large-scale integrated circuits and chip manufacturing. At present, domestic ultra-clean high-purity citric acid mainly relies on imports, and domestically produced citric acid is difficult to meet the ultra-clean high-purity citric acid standards.
[0004] The common purification processes for citric acid are ion exchange resin method and crystallization method. The combination of these two methods is the conventional production process for food-grade citric acid. The content of light metal ions such as Na, K, Ca, etc. in food-grade citric acid is at the ppm level, which means that in order to obtain ultra-clean high-purity citric acid, it is necessary to deeply purify the food-grade citric acid. The ion exchange resin method is a common purification method, which mainly relies on the H + Replace cations and OH in citric acid - / HCO3 - Replace the anionic impurities in citric acid to purify the citric acid. The ion exchange resin method has significant advantages in removing heavy metals (Fe, Ag, Cr, etc.), but the removal effect on general light metal ions (Na, K, Ca, etc.) is slightly weaker. High-performance ion exchange resins that can achieve deep removal of metal ions are still imported, and the performance of domestic ion exchange resins is difficult to use in the preparation of ultra-clean and high-purity citric acid. Crystallization is one of the important methods for refining solid compounds, but the purity of crystals obtained from a single crystallization is often not high. Crystals with higher purity can only be obtained after multiple recrystallizations. However, multiple recrystallizations often bring about problems such as high energy consumption and low yield, which have certain limitations in the purification of ultra-clean and high-purity citric acid.
[0005] Nanofiltration is an emerging membrane separation technology. The pore size range of nanofiltration membrane is between reverse osmosis membrane and ultrafiltration membrane. The characteristics of nanofiltration technology are: it can intercept organic matter and multivalent ions with a molecular weight greater than 200, and allow small molecular organic matter and monovalent ions to pass through; it can operate under harsh conditions such as high temperature, acid, and alkali, and the membrane can tolerate a wide range of conditions, high concentration multiples, and pollution resistance; the operating pressure is low, the membrane flux is high, the device operating cost is low, and the energy consumption is low. Nanofiltration technology has great potential in removing light metal ion impurities in citric acid.
[0006] Based on the characteristics of citric acid purification process and nanofiltration technology, nanofiltration technology is organically coupled with ion exchange resin method, and nanofiltration technology is used to selectively remove light metal ions (Na, K, Ca, etc.) in citric acid, and other easily removable impurities are removed by ion exchange resin method. The application of nanofiltration technology can reduce the requirements of ion exchange process on the performance of ion exchange resin, extend the life of ion exchange resin, and reduce the cost of ion exchange resin to a certain extent. It is a more economical and feasible ultra-clean high-purity citric acid production process compared with the current citric acid purification method. Summary of the invention
[0007] Aiming at the problem that metal ions cannot be effectively removed in the current citric acid purification process to prepare ultra-clean high-purity citric acid, the present invention provides an ultra-clean high-purity citric acid and a production process thereof. The ultra-clean high-purity citric acid is an aqueous solution of citric acid, and the metal ion content in the product is less than 1 ppb.
[0008] The ultra-clean high-purity citric acid production process provided by the present invention mainly includes: ① dissolution, ② nanofiltration, and ③ ion exchange resin adsorption. The specific process is: ① use ultrapure water to prepare industrial-grade or food-grade citric acid into a citric acid solution; ② remove monovalent light metal ions in the citric acid solution by nanofiltration technology, and concentrate the citric acid solution to a certain concentration to obtain a citric acid filtration concentrate; ③ pass the citric acid filtration concentrate through anion exchange resin, cation exchange resin, and mixed bed polishing resin under appropriate conditions to deeply remove anion and cation impurities in the citric acid concentrate, and finally obtain an ultra-clean high-purity citric acid product. The application of nanofiltration technology can significantly reduce the performance requirements of the ion exchange process for the cation exchange resin, and can also extend the service life of the cation exchange resin.
[0009] In the above step ① of dissolving, the mass concentration of the prepared citric acid solution is 10-20%, preferably 15%.
[0010] In the above step ② nanofiltration, the citric acid solution is concentrated by nanofiltration to a mass concentration of 30-40%, preferably 35%.
[0011] In the above step ③ of ion exchange resin adsorption, the anion exchange resin is a strong base gel type SA680N, the cation exchange resin is a strong acid macroporous type ZGC151, and the mixed bed polishing resin is SC990N and ZGA351MB mixed and filled in a certain proportion.
[0012] As a preferred solution, the mixed bed polishing resin is a mixture of SC990N and ZGA351MB in a volume ratio of 1:2-5, and the preferred volume ratio of SC990N to ZGA351MB is 1:3.
[0013] As a preferred solution, the flow rate of the citric acid solution passing through the anion exchange resin is 1 to 5 BV / h, and the preferred flow rate of the citric acid solution passing through the anion exchange resin is 2 BV / h.
[0014] As a preferred solution, the flow rate of the citric acid solution passing through the cation exchange resin is 5 to 10 BV / h, and the preferred flow rate of the citric acid solution passing through the cation exchange resin is 6 BV / h.
[0015] As a preferred solution, the flow rate of the citric acid solution through the mixed bed polishing resin is 3 to 8 BV / h, and the preferred flow rate of the citric acid solution through the mixed bed polishing resin is 5 BV / h.
[0016] The specific operation of the nanofiltration part in the above process is as follows:
[0017] (1) First, use ultrapure water to thoroughly clean the nanofiltration system until the conductivity of the produced water and concentrated water is no higher than 0.1us / cm;
[0018] (2) The nanofiltration membrane of the nanofiltration system is NF270. According to the effective membrane area of the nanofiltration component, the citric acid feed flow rate is set to 20 L·m -2 ·h -1 By controlling the flow rate of citric acid filtration concentrate, different concentration multiples of the nanofiltration system can be achieved.
[0019] The nanofiltration membrane has the characteristic of selectively intercepting macromolecules and high-valent metal ions, which can selectively remove some monovalent light metal ions in citric acid, reduce the subsequent ion exchange resin load, and thus reduce the cost of the ion exchange process. At present, Dow nanofiltration membrane technology is mature, and commercial nanofiltration membranes represented by NF270 and NF90 have been widely used in chemical, water treatment, pharmaceutical and other industries. The present invention is the first to couple nanofiltration technology with ion exchange technology in the field of citric acid purification.
[0020] Specific operation of the ion exchange part in the above process
[0021] (1) Use ultrapure water to flush the entire ion exchange system to ensure that there is no ion dissolution from the anion, cation, and mixed bed ion exchange resins;
[0022] (2) The citric acid filtered concentrate was passed through an anion exchange resin column filled with SA680N, a cation exchange resin column with ZGC151, and a mixed bed polishing resin column filled with SC990N and ZGC351MB at a certain flow rate, and the solution temperature was controlled at 25±5°C;
[0023] (3) The first 1 to 2 BV of purified liquid that passed through the column was discarded, and the ion exchange purified liquid was collected starting from the 3rd BV.
[0024] Cation exchange resin column and mixed bed polishing resin column can finally obtain ultra-clean high-purity citric acid.
[0025] Since citric acid itself has a strong ability to chelate metal ions, the entire ion exchange system must be fully rinsed with ultrapure water before use to ensure that no additional impurities are introduced into the system. Metal ions and other anionic impurities in the citric acid filtrate concentrate can be removed by ion exchange resin to obtain an ultra-clean high-purity citric acid product. The ultra-clean high-purity citric acid prepared by the preparation method of the present invention is an aqueous solution of citric acid, and the metal ion content in the citric acid solution is less than 1ppb.
[0026] The above-mentioned process of combining nanofiltration and ion exchange has not been reported in the field of citric acid purification, and the key points involved in the process, such as nanofiltration membrane model, ion exchange resin model and formula, are also proposed for the first time in the present invention. In the early stage of process research and development, the present invention encountered many problems in the selection of ion exchange resins, such as: low metal ion removal rate; high metal ion removal rate, but short life; high anion removal rate of anion exchange resin, but high cation dissolution; low removal rate of low-content metal ions by mixed bed resin, and the presence of anion, cation or TOC dissolution. After a long period of technical research, the inventor screened out the nanofiltration membrane NF270 suitable for separating low-valent metal ions in citric acid, and benefited from the great role of nanofiltration technology in removing a large number of low-valent impurities in citric acid, the life of ZGC151 with high metal ion removal rate but short life was significantly extended. At the same time, the inventor designed a mixed bed polishing resin formula, mixed SC990N and ZGA351MB in a certain volume ratio, and obtained a mixed bed polishing resin with excellent performance. Finally, through long-term optimization of nanofiltration and ion exchange related processes (such as concentration multiple, column temperature, flow rate, etc.), the optimal related process parameters were obtained, and the stable preparation of ultra-clean and high-purity citric acid was achieved. DETAILED DESCRIPTION
[0027] The above contents of the present invention are further described in detail below through specific embodiments, but it should not be understood that the scope of the above subject matter of the present invention is limited to the following embodiments. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. The present invention is further described below in conjunction with the embodiments.
[0028] Example 1
[0029] The main process includes the following main steps:
[0030] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 15% for standby use.
[0031] 2) Nanofiltration: 15 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 35 wt% by the nanofiltration system. The nanofiltration membrane component was NF270, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0032] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:3 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 5BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0033] It should be noted that the pipes, valves, containers, etc. involved in this process route are all lined with PFA or PTFE to avoid additional contamination introduced into the device as much as possible.
[0034] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0035] Table 1. Analysis and test results
[0036] project unit result project unit result Li ppb 0.83 As ppb 0.19 Na ppb 0.67 Sr ppb 0.11 Mg ppb 0.55 Ag ppb 0.31 Al ppb 0.39 Cd ppb 0.24 K ppb 0.48 Ba ppb 0.08 Ca ppb 0.69 Ti ppb 0.11 Cr ppb 0.24 Pb ppb 0.12 Mn ppb 0.52 Fe ppb 0.45 <![CDATA[SO4 2- ]]> ppb 8.72 Co ppb 0.38 <![CDATA[NO3 - ]]> ppb 6.57 Ni ppb 0.25 <![CDATA[Cl - ]]> ppb 5.67 Cu ppb 0.23 <![CDATA[F - ]]> ppb 4.58 Zn ppb 0.32 Ga ppb 0.18 life BV 30
[0037] The process parameters of this embodiment are preferred parameters, achieving a perfect balance between the citric acid impurity ion removal rate, purification efficiency, and ion exchange resin life. The metal ion impurity content in the citric acid solution prepared under this process condition is less than 1 ppb, the anion impurity content is less than 10 ppb, and the ion exchange resin life is as high as 30 BV. Undoubtedly, nanofiltration technology coupled with ion exchange technology provides a new idea for the preparation of ultra-clean and high-purity citric acid.
[0038] Example 2
[0039] The main process includes the following main steps:
[0040] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 15% for standby use.
[0041] 2) Nanofiltration: 15 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 40 wt% by the nanofiltration system. The nanofiltration membrane component was NF270, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0042] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous type ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:2 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 3BV / h, the flow rate through the cation exchange resin tower is 8BV / h, and the flow rate through the mixed bed polishing resin tower is 6BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0043] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0044] Table 2. Analysis and test results
[0045] project unit result project unit result Li ppb 29.84 As ppb 0.35 Na ppb 0.91 Sr ppb 0.29 Mg ppb 0.81 Ag ppb 0.68 Al ppb 0.79 Cd ppb 0.37 K ppb 0.79 Ba ppb 0.26 Ca ppb 0.75 Ti ppb 0.32 Cr ppb 0.92 Pb ppb 0.32 Mn ppb 0.41 Fe ppb 0.61 <![CDATA[SO4 2- ]]> ppb 9.37 Co ppb 0.64 <![CDATA[NO3 - ]]> ppb 7.33 Ni ppb 0.58 <![CDATA[Cl - ]]> ppb 6.13 Cu ppb 0.41 <![CDATA[F - ]]> ppb 5.03 Zn ppb 0.41 Ga ppb 0.52 life BV 30
[0046] The characteristic of this embodiment is that the nanofiltration and ion exchange process conditions are changed, specifically, the nanofiltration concentration multiple and the ion exchange process column speed are slightly improved. From the analysis and test results in Table 2, it can be seen that high concentration multiples and high ion exchange speeds will have a certain negative impact on the purification effect, but the metal ion content in the obtained citric acid product is still less than 1ppb.
[0047] Example 3
[0048] The main process includes the following main steps:
[0049] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 20% for standby use.
[0050] 2) Nanofiltration: Pump 20 wt% citric acid solution into the nanofiltration system, and concentrate the citric acid solution to 40 wt% through the nanofiltration system. The nanofiltration membrane component is NF270, and collect the concentrated liquid of the nanofiltration system in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0051] 3) Ion exchange: Pump the citric acid nanofiltration concentrate into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous type ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:4 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 8BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0052] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0053] Table 3. Analysis and test results
[0054] project unit result project unit result Li ppb 0.88 As ppb 0.31 Na ppb 0.84 Sr ppb 0.23 Mg ppb 0.72 Ag ppb 0.67 Al ppb 0.66 Cd ppb 0.33 K ppb 0.71 Ba ppb 0.21 Ca ppb 0.83 Ti ppb 0.29 Cr ppb 0.33 Pb ppb 0.31 Mn ppb 0.58 Fe ppb 0.63 <![CDATA[SO4 2- ]]> ppb 9.02 Co ppb 0.54 <![CDATA[NO3 - ]]> ppb 7.31 Ni ppb 0.36 <![CDATA[Cl - ]]> ppb 6.02 Cu ppb 0.34 <![CDATA[F - ]]> ppb 4.93 Zn ppb 0.46 Ga ppb 0.38 life BV 30
[0055] The nanofiltration and ion exchange process in this embodiment is an intermediate process condition, specifically, the nanofiltration concentration ratio is slightly reduced, the column speed of the mixed bed resin is increased, and the proportion of ZGC351MB in the mixed bed resin is increased. From the results in Table 3, it can be seen that the metal ion content in citric acid has increased slightly compared with the preferred process, but the overall metal ion content is still less than 1ppb, and this process parameter can still be used to prepare ultra-clean high-purity citric acid.
[0056] Example 4
[0057] The main process includes the following main steps:
[0058] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 15% for standby use.
[0059] 2) Nanofiltration: 15 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 35 wt% by the nanofiltration system. The nanofiltration membrane component was NF270, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0060] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous type ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:5 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 1BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 5BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0061] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0062] Table 4. Analysis and test results
[0063] project unit result project unit result Li ppb 0.84 As ppb 0.23 Na ppb 0.71 Sr ppb 0.19 Mg ppb 0.68 Ag ppb 0.44 Al ppb 0.45 Cd ppb 0.26 K ppb 0.65 Ba ppb 0.12 Ca ppb 0.77 Ti ppb 0.21 Cr ppb 0.31 Pb ppb 0.26 Mn ppb 0.55 Fe ppb 0.59 <![CDATA[SO4 2- ]]> ppb 8.92 Co ppb 0.43 <![CDATA[NO3 - ]]> ppb 7.01 Ni ppb 0.31 <![CDATA[Cl - ]]> ppb 5.98 Cu ppb 0.30 <![CDATA[F - ]]> ppb 4.87 Zn ppb 0.45 Ga ppb 0.33 life BV 30
[0064] The nanofiltration process in this embodiment is the preferred process, but the ion exchange column speed is significantly reduced, and the loading ratio of the two mixed bed resins is adjusted. As can be seen from the results in Table 4, the metal ion content in the citric acid product is relatively low, but it should be noted that the reduction in column speed will significantly reduce the citric acid purification efficiency, which obviously has certain limitations in the pursuit of production efficiency.
[0065] Example 5
[0066] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 10% for standby use.
[0067] 2) Nanofiltration: 10 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 30 wt% by the nanofiltration system. The nanofiltration membrane component was NF270, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0068] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous type ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:3 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 10BV / h, and the flow rate through the mixed bed polishing resin tower is 8BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0069] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0070] Table 5. Analysis and test results
[0071] project unit result project unit result Li ppb 0.98 As ppb 0.40 Na ppb 0.89 Sr ppb 0.43 Mg ppb 0.84 Ag ppb 0.89 Al ppb 0.78 Cd ppb 0.41 K ppb 0.83 Ba ppb 0.27 Ca ppb 0.93 Ti ppb 0.40 Cr ppb 0.54 Pb ppb 0.34 Mn ppb 0.72 Fe ppb 0.72 <![CDATA[SO4 2- ]]> ppb 9.44 Co ppb 0.63 <![CDATA[NO3 - ]]> ppb 7.41 Ni ppb 0.52 <![CDATA[Cl - ]]> ppb 6.22 Cu ppb 0.57 <![CDATA[F - ]]> ppb 5.12 Zn ppb 0.78 Ga ppb 0.41 life BV 30
[0072] This embodiment improves the nanofiltration concentration multiple and the ion exchange column speed. As can be seen from the results in Table 5, the metal ion impurity content of the citric acid product has increased to a certain extent, but is still less than 1 ppb. The increase in the ion exchange column speed is conducive to improving the citric acid purification efficiency, but a faster column speed may affect the ion exchange purification effect to a certain extent.
[0073] Comparative Example 1
[0074] The citric acid was purified using ion exchange resins only without using nanofiltration technology.
[0075] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 35% for standby use.
[0076] 2) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous type ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:3 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 5BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0077] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0078] Table 6. Analysis and test results
[0079] project unit result project unit result Li ppb 6.68 As ppb 1.10 Na ppb 5.52 Sr ppb 1.04 Mg ppb 4.33 Ag ppb 1.66 Al ppb 3.88 Cd ppb 1.78 K ppb 5.30 Ba ppb 1.13 Ca ppb 5.32 Ti ppb 1.11 Cr ppb 2.75 Pb ppb 1.28 Mn ppb 1.57 Fe ppb 2.71 <![CDATA[SO4 2- ]]> ppb 7.43 Co ppb 2.19 <![CDATA[NO3 - ]]> ppb 7.32 Ni ppb 1.58 <![CDATA[Cl - ]]> ppb 6.12 Cu ppb 2.61 <![CDATA[F - ]]> ppb 5.97 Zn ppb 3.58 Ga ppb 1.30 life BV 20
[0080] This comparative example does not use nanofiltration technology, but only uses ion exchange technology, and the ion exchange column speed is the preferred process. As can be seen from the results in Table 6, the citric acid product prepared by using only ion exchange technology without using nanofiltration technology has a metal ion content far higher than 1ppb, and due to the large load of ion exchange resin, the life of ion exchange resin is seriously shortened.
[0081] Comparative Example 2
[0082] This comparative example uses nanofiltration technology, but the nanofiltration membrane is NF90, which has a lower selectivity for monovalent and divalent ions than NF270.
[0083] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 15% for standby use.
[0084] 2) Nanofiltration: 10 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 35 wt% by the nanofiltration system. The nanofiltration membrane component was NF90, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0085] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:3 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 5BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0086] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0087] Table 7. Analysis and test results
[0088] project unit result project unit result Li ppb 1.81 As ppb 1.94 Na ppb 1.69 Sr ppb 1.09 Mg ppb 1.61 Ag ppb 3.71 Al ppb 1.38 Cd ppb 1.28 K ppb 1.47 Ba ppb 1.11 Ca ppb 1.73 Ti ppb 1.09 Cr ppb 1.20 Pb ppb 1.10 Mn ppb 1.49 Fe ppb 1.44 <![CDATA[SO4 2- ]]> ppb 10.55 Co ppb 1.36 <![CDATA[NO3 - ]]> ppb 9.01 Ni ppb 1.26 <![CDATA[Cl - ]]> ppb 8.54 Cu ppb 1.23 <![CDATA[F - ]]> ppb 5.61 Zn ppb 1.72 Ga ppb 1.18 life BV 25
[0089] The ion exchange process of this comparative example uses the preferred process, and the nanofiltration process only replaces the nanofiltration membrane with NF90 with lower selectivity for monovalent and divalent ions. As can be seen from the results in Table 7, the contents of all metal ions are high, and the life of the ion exchange resin is reduced. The reason is that the monovalent and divalent ion selectivity of NF90 is poor, and the selective separation of monovalent and divalent ions cannot be achieved, resulting in a large amount of monovalent ion impurities in the citric acid solution after nanofiltration concentration, which affects the subsequent ion exchange effect.
[0090] Comparative Example 3
[0091] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 5% for standby use.
[0092] 2) Nanofiltration: Pump 20 wt% citric acid solution into the nanofiltration system, and concentrate the citric acid solution to 45 wt% through the nanofiltration system. The nanofiltration membrane component is NF270, and collect the concentrated liquid of the nanofiltration system in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0093] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:3 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 5BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0094] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0095] Table 8. Analysis and test results
[0096] project unit result project unit result Li ppb 2.84 As ppb 2.31 Na ppb 2.66 Sr ppb 2.21 Mg ppb 2.57 Ag ppb 1.44 Al ppb 3.41 Cd ppb 1.31 K ppb 3.52 Ba ppb 2.19 Ca ppb 3.77 Ti ppb 1.28 Cr ppb 2.23 Pb ppb 1.23 Mn ppb 2.54 Fe ppb 3.61 <![CDATA[SO4 2- ]]> ppb 10.12 Co ppb 3.51 <![CDATA[NO3 - ]]> ppb 7.86 Ni ppb 2.48 <![CDATA[Cl - ]]> ppb 6.98 Cu ppb 1.53 <![CDATA[F - ]]> ppb 6.45 Zn ppb 2.46 Ga ppb 3.33 life BV 18
[0097] The characteristic of this comparative example is to significantly increase the nanofiltration concentration multiple to examine the boundary condition parameters of the nanofiltration process. The preferred nanofiltration concentration multiple should remove metal ion impurities in the citric acid solution as much as possible to reduce the load of the ion exchange resin in the later stage. It can be seen from the analysis and test results in Table 8 that when the nanofiltration concentration multiple is increased, the metal ion content in the obtained citric acid solution increases to a certain extent. It is not difficult to see that as a pre-process of the ion exchange process, the nanofiltration concentration multiple cannot be too high, otherwise it will lead to a decrease in the removal rate of light metal ions and excessive concentration of heavy metal ions, which will lead to a decrease in the metal ion removal rate and resin life of the ion exchange resin.
[0098] Comparative Example 4
[0099] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 15% for standby use.
[0100] 2) Nanofiltration: 15 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 35 wt% by the nanofiltration system. The nanofiltration membrane component was NF270, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0101] 3) Ion exchange: The citric acid nanofiltration concentrate is pumped into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous type ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:7 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 2BV / h, the flow rate through the cation exchange resin tower is 6BV / h, and the flow rate through the mixed bed polishing resin tower is 5BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0102] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0103] Table 9. Analysis and test results
[0104] project unit result project unit result Li ppb 5.30 As ppb 2.10 Na ppb 4.23 Sr ppb 1.87 Mg ppb 3.87 Ag ppb 1.72 Al ppb 3.56 Cd ppb 1.84 K ppb 4.54 Ba ppb 1.66 Ca ppb 4.78 Ti ppb 1.36 Cr ppb 2.88 Pb ppb 1.56 Mn ppb 2.78 Fe ppb 3.57 <![CDATA[SO4 2- ]]> ppb 9.97 Co ppb 3.24 <![CDATA[NO3 - ]]> ppb 7.94 Ni ppb 2.79 <![CDATA[Cl - ]]> ppb 8.21 Cu ppb 2.58 <![CDATA[F - ]]> ppb 5.14 Zn ppb 3.67 Ga ppb 2.32 life BV 30
[0105] The nanofiltration process conditions of this comparative example are the preferred process conditions, which change the ratio of the mixed filling of the two mixed bed resins. As can be seen from the results in Table 9, all metal ion contents and anion contents have increased to a certain extent. It should be noted that the increase in metal ions under this condition is not due to the poor nanofiltration and anion and cation exchange effects, but due to the change in the filling ratio of SC99ON and ZGC351MB, which leads to the dissolution of metal ions in the mixed filling resin, and finally leads to the excessive impurity content in the obtained citric acid product. Therefore, a reasonable mixed bed resin filling ratio is crucial to the quality of the final citric acid product.
[0106] Comparative Example 5
[0107] 1) Dissolution: Use ultrapure water to prepare food-grade citric acid into an aqueous solution with a mass concentration of 15% for standby use.
[0108] 2) Nanofiltration: 15 wt% citric acid solution was pumped into the nanofiltration system, and the citric acid solution was concentrated to 35 wt% by the nanofiltration system. The nanofiltration membrane component was NF270, and the concentrated liquid of the nanofiltration system was collected in a citric acid nanofiltration concentrated liquid storage tank for standby use.
[0109] 3) Ion exchange: Pump the citric acid nanofiltration concentrate into an ion exchange system consisting of a resin tower filled with a strong base gel type SA680N anion exchange resin, a resin tower filled with a strong acid macroporous ZGC151 cation exchange resin, and a mixed bed polishing resin tower filled with SC99ON and ZGC351MB in a volume ratio of 1:3 in series. The flow rate of the citric acid nanofiltration concentrate through the anion resin tower is 7BV / h, the flow rate through the cation exchange resin tower is 15BV / h, and the flow rate through the mixed bed polishing resin tower is 10BV / h. The citric acid ion exchange liquid is collected and stored in a storage tank.
[0110] The obtained citric acid product was analyzed for total metal ion content using ICP-MS. The obtained citric acid product was tested for anion content using IC. When the metal ion content in the citric acid product was >5 ppb, the cation exchange resin was judged to have terminated its service life.
[0111] Table 10. Analysis and test results
[0112] project unit result project unit result Li ppb 4.03 As ppb 2.61 Na ppb 3.12 Sr ppb 2.22 Mg ppb 3.11 Ag ppb 1.49 Al ppb 3.30 Cd ppb 2.10 K ppb 4.46 Ba ppb 2.63 Ca ppb 4.73 Ti ppb 1.74 Cr ppb 2.98 Pb ppb 2.10 Mn ppb 3.99 Fe ppb 4.46 <![CDATA[SO4 2- ]]> ppb 10.45 Co ppb 4.59 <![CDATA[NO3 - ]]> ppb 8.65 Ni ppb 3.22 <![CDATA[Cl - ]]> ppb 7.34 Cu ppb 2.11 <![CDATA[F - ]]> ppb 6.89 Zn ppb 3.85 Ga ppb 4.02 life BV 30
[0113] The nanofiltration process conditions of this comparative example are the preferred process conditions, which significantly improve the ion exchange column speed. As can be seen from the results in Table 10, all metal ion contents and anion contents are relatively high, and the purity deviation of the citric acid product prepared by the preferred process is relatively large. It can be seen that the ion exchange column speed cannot be too fast, otherwise it will affect the ion exchange purification effect.
[0114] In summary, the method for preparing ultra-clean and high-purity citric acid provided by the present invention requires the efficient coupling of nanofiltration technology and ion exchange technology. The two complement each other and achieve efficient removal of trace impurities in citric acid. When only one of the technologies is used or the two technologies have a poor match, the stable preparation of ultra-clean and high-purity citric acid cannot be achieved.
[0115] The above description is only the preferred embodiment and comparative example of the present invention, and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing ultra-clean high-purity lemons, characterized in that: Follow these steps: (1) Dissolution: Use an appropriate amount of ultrapure water to prepare a citric acid solution of appropriate concentration; (2) Nanofiltration: Preliminarily concentrate the solution obtained in step (1) through a nanofiltration membrane, and recover the nanofiltration concentrate. The nanofiltration membrane is NF270; (3) Ion exchange: The nanofiltration concentrate obtained in step (2) is passed through an anion exchange resin column, a cation exchange resin column, and a mixed bed polishing resin column at an appropriate flow rate, and finally ultra-clean high-purity citric acid is obtained. The anion exchange resin is a strong base gel type SA680N, the cation exchange resin is a strong acid macroporous type ZGC151, and the mixed bed polishing resin is SC990N and ZGA351MB mixed and filled in a certain volume ratio.
2. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (1), the citric acid is industrial grade or food grade citric acid; the mass concentration of the prepared citric acid solution is 10-20%.
3. The method for preparing ultra-clean high-purity citric acid according to claim 2, characterized in that: In step (1), the citric acid is industrial grade or food grade citric acid; the mass concentration of the prepared citric acid solution is 15%.
4. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (2), the feed flow rate of citric acid into the nanofiltration membrane is set to 10-20 L·m -2 ·h -1 .
5. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: Step (2) The citric acid solution is concentrated by nanofiltration to a mass concentration of 30-40%.
6. The method for preparing ultra-clean high-purity citric acid according to claim 5, characterized in that: Step (2) The citric acid solution is concentrated by nanofiltration to a mass concentration of 35%.
7. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: The mixed bed polishing resin is a mixed resin prepared by mixing SC990N and ZGA351MB in a volume ratio of 1:2-5.
8. The method for preparing ultra-clean high-purity citric acid according to claim 7, characterized in that: The mixed bed polishing resin is a mixed resin prepared by mixing SC990N and ZGA351MB in a volume ratio of 1:
3.
9. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (3), the flow rate of the citric acid solution passing through the anion exchange resin is 1-5 BV / h.
10. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (3), the flow rate of the citric acid solution through the anion exchange resin is 2 BV / h.
11. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (3), the flow rate of the citric acid solution passing through the cation exchange resin is 5-10 BV / h.
12. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (3), the flow rate of the citric acid solution passing through the cation exchange resin is 6 BV / h.
13. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (3), the flow rate of the citric acid solution through the mixed bed polishing resin is 3-8 BV / h.
14. The method for preparing ultra-clean high-purity citric acid according to claim 1, characterized in that: In step (3), the flow rate of the citric acid solution through the mixed bed polishing resin is 5 BV / h.
15. The preparation method according to any one of claims 1 to 14, characterized in that: The prepared ultra-clean high-purity citric acid is an aqueous solution of citric acid, and the metal ion content in the citric acid solution is less than 1 ppb.
Citation Information
Patent Citations
Electronic grade citric acid and production method thereof
CN101973871A
Method for extracting citric acid from citric acid fermentation liquid by utilizing nanofiltration membrane
CN105111069A